Filter-less submicron hydrodynamic size sorting. Issue 4 (18th January 2016) - Fouet, M.; Mader, M.-A.; Iraïn, S.; Yanha, Z.; Naillon, A.; Cargou, S.; Gué, A.-M.; Joseph, P.
Abstract : We push the limits of hydrodynamic filtration by demonstrating filter-less sorting of submicron particles, in line with the model and simulations. Abstract : We propose a simple microfluidic device able to separate submicron particles (critical size ∼0.1 μm) from a complex sample with no filter (minimum channel dimension being 5 μm) by hydrodynamic filtration. A model taking into account the actual velocity profile and hydrodynamic resistances enables prediction of the chip sorting properties for any geometry. Two design families are studied to obtain (i) small sizes within minutes (low-aspect ratio, two-level chip) and (ii) micron-sized sorting with a μL flow rate (3D architecture based on lamination). We obtain quantitative agreement of sorting performances both with experiments and with numerical solving, and determine the limits of the approach. We therefore demonstrate a passive, filter-less sub-micron size sorting with a simple, robust, and easy to fabricate design.